PENGARUH FAKTOR-FAKTOR EKSTERNAL DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PONSEL NOKIA - Andhika Putra Kurniawan (FE 06 UMY, 2006)
PENGARUH FAKTOR-FAKTOR EKSTERNAL DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PONSEL NOKIA